Ascertaining the Meaning of Legislation - A Question of Context - Nijman, Cathy (Victoria University of Wellington Law Review, 2007)
It has been said that "no word in an Act can be safely interpreted out of its context". Yet, Parliament was sufficiently concerned about the courts' use of external context as an aid to statutory interpretation to decide consciously to omit reference to "context" when enacting section 5(1) of the Interpretation Act 1999. This paper investigates the reasons for Parliament's concern. It examines cases decided before and after the enactment of section 5(1) to establish past and present judicial practice when using external context as an interpretive aid. The paper concludes that the omission of "context from section 5(1) has not altered the courts' principled approach to matters of interpretation, and it demonstrates that consideration of external context is an essential corollary to the purposive approach to statutory interpretation mandated by Parliament for over 100 years.